Evaluation of sunscreen efficacy over time and re‐application using hybrid diffuse reflectance spectroscopy - Ruvolo, Eduardo; Aeschliman, Lisa; Cole, Curtis (Photodermatology, photoimmunology & photomedicine, 2020)
Background In 2007, the FDA added requirements for sunscreens to be labeled “re‐apply at least every 2 hours” based on very limited data. This study used hybrid diffuse reflectance spectroscopy (HDRS) to evaluate the persistence of protection by 80 minutes water‐resistant sunscreen formulation with and without re‐application, and with and without sweat‐inducing activity over 6 hours. Methods Sunscreens were applied to subject's foreheads and backs, and they remained at rest or exercised to induce sweating in a heated environment. Efficacy of a sun protection factor (SPF 50) very water‐resistant sunscreen was measured with HDRS instrumentation and ultraviolet (UV) photography to determine the sunscreen protection over time. Results The sunscreen maintained SPF 50 efficacy over 6 hours for the non‐active group with a single application, and for 2 hours for the active group, dropping slowly to SPF 30 level after 6 hours of sweating. Re‐application of sunscreen gave additive SPF, with two applications resulting in SPF >100 and three applications approximately SPF 150. UV photography was insensitive to the differences in protection detected with HDRS instrumentation. Conclusions Sunscreen efficacy is maintained over time in the absence of sweating or rub‐off. After two hours of sweating, an 80 minutes water‐resistant sunscreen does not need to be re‐applied “at least every 2 hours.”